The Role of Linguistic Routines in Early Foreign Language Learning - Michele Daloiso (Escola Superior de Educação de Paula Frassinetti, 2009)
According to recent studies in neuropsychology, when learning a language, young children mainly use "implicit memory", i.e. the memory of automatic procedures such as riding a bicycle. As an implication for early foreign language teaching (EFLT), teachers will stimulate the pupils' implicit memory by exposing them to routine situations in which specific linguistic expressions are associated with recurring actions and procedures. This paper will therefore discuss the neuropsychological, linguistic and educational roles of routines in EFLT and will provide teachers with methodological principles to manage routine situations in a foreign language.